N-term 2017: Proteostasis via the N-terminus - Dissmeyer, Nico; Graciet, Emmanuelle; Holdsworth, Michael J.; Gibbs, Daniel J. (Elsevier, 2017)
N-term 2017 was the first international meeting to bring together researchers from diverse disciplines with a shared interest in protein N-terminal modifications and the N-end rule pathway of ubiquitin-mediated proteolysis, providing a platform for interdisciplinary cross-kingdom discussions and collaborations, as well as strengthening the visibility of this growing scientific community.